METABOLIC SURGERY IN CORRECTION OF FATTY LIVER DISEASE - M. B. Fishman; V. E. Karev; V. Yan; D. A. Sokolova; A. I. Mitsinskaya; M. A. Mitsinskiy (Вестник хирургии имени И.И. Грекова)
The article presents the results of treatment of 68 patients who underwent laparoscopic sleeve gastric resection (LSG) and laparoscopic gastric bypass (LGB) at the period from 2014 to 2015. The efficacy of operations on the course of nonalcoholic fatty liver disease (NAFLD) was estimated. There were performed a liver biopsy and histological studies with determination of histological activity index, the rate of severity of fibrosis according R. G. Knodell scale and METAVIR system, nature and degree of manifestation of steatosis of hepatocytes and intrahepatic cholestasis. NAS activity scale was used to evaluate morphological changes. The results of 1,5-year follow-up study were assessed in dynamics. Fibro Test results were in the range from 0 to 1 depending of fibrosis severity using METAVIR system (from F0 to F4), Knodell and Ishak scales. It was stated that there was an improvement of histological and functional findings in cases of hepatic steatosis, inflammation and fibrosis. All the patients (100%) initially had the signs of NAFLD and 12 patients (22,6%) - fibrosis. The complete regression of NAFLD was noted in 43(81,1%) cases and signs of previous fibrosis were smoothed over in 6 patients (41%). Liver function tests have deteriorated at 6-month period, but tests improved to normal rates at the end of 1-year period. The bariatric surgeries are effective methods of NAFLD treatment and Fibro Test is non-invasive and reliable method of liver state assessment.